Picturing the barrio : ten Chicano photographers - Foster, David William (Latino and Latin American profiles., 2017)
"Mexican-American life, like that of nearly every contemporary community, has been extensively photographed. Yet there is surprisingly little scholarship on Chicano photography. Picturing the Barrio presents the first book-length examination on the topic. David William Foster analyzes the imagery of ten distinctive artists who offer a range of approaches to portraying Chicano life. The production of each artist is examined as an ideological interpretation of how Chicano experience is constructed and interpreted through the medium of photography, in sites ranging from the traditional barrio to large metropolitan societies. These photographers present artistic as well as documentary images of the socially invisible. They and their subjects grapple with definitions of identity, as well as ethnicity and gender. As such, this study deepens our understanding of the many interpretations of the Chicano experience"--Provided by publisher.